PENGARUH BEBAN KERJA, KUALITAS KEHIDUPAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI BPBD KABUPATEN JEMBER - Ema Desia Prajitiasari; Gusti Ayu Wulandari; Vellya Wahyu Nur Istianti (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of workload, work-life quality, and organizational commitment on employee performance at the Regional Disaster Management Agency (BPBD) of Jember Regency. The research sample consisted of 60 BPBD employees of Jember Regency, which was taken based on the census sampling technique. Data were analyzed using multiple linear regression. The results showed that workload, work-life quality, and organizational commitment had a significant positive effect on the performance of BPBD employees in Jember Regency. Therefore, BPBD Jember should design the workload according to performance standards, improve the quality of the physical work environment, and involve employees in every performance improvement discussion to increase organizational commitment. Keywords : organizational commitment, performance, work-life quality, workload